Risks and Risk Management Strategies in Rubber Farming: Evidence from New Areas of Northeastern in Thailand - Kongmanee, Chaiya; Ahmed, Ferdoushi (Journal of Cultural Analysis and Social Change, 2026)
Rubber plantations in Northeastern Thailand play a central role in poverty reduction, income generation, and rural livelihoods. Farmers in these areas face diverse risks that threaten production and income stability, making effective risk management essential. This study aims to identify key risks, examine the strategies used by farmers to manage them, and analyze the relationships between risk factors and management responses. Data were collected through structured household interviews with 260 farmers selected purposively from Ubon Ratchathani and Bueng Kan provinces. Factor analysis was employed to identify the dimensions of risk and management strategies, while path analysis was used to examine their interrelationships. The results revealed seven categories of risk: technical and management, production, price and market, natural disaster, income, middleman, and farm skill and competency. These factors together explained 63.63 percent of the total variance. Farmers adopted eight main categories of management strategies: participation in government programs, improvement of farm skills and workforces, sale of high-quality rubber through auction markets, flexible tapping systems, updated market and production information, engagement in farmer groups, household financial and debt management, and production diversification. These strategies explained 60.64 percent of the variance. Price and market risks were perceived at the highest level. They were positively associated with reliance on updated production and market information, and negatively associated with participation in government programs, auction market sales, and structured debt management. The findings suggest that most farmers are risk averse and rely primarily on reactive coping strategies rather than proactive approaches. To strengthen resilience, government support should move beyond short term assistance toward proactive strategies that include price stabilization mechanisms, forward contracts, income diversification, and climate adaptive practices.